Role of LMS-Based Learning Communities on the Independent Teaching Platform in Enhancing Teachers’ Basic Competencies - Sri Jumini; Parmin Parmin; Asri Widowati; Wahyudi Wahyudi; Öznur ATAŞ AKDEMİR; Ahmet Selçuk AKDEMİR; Fatih Can; Berk İlhan; Victor Oluwatosin Ajayi; Odessa D. Aberilla; Winarto Winarto; Purba Risma Sutikno (Online Learning In Educational Research (OLER), 2026)
This study aims to analyze the role of the Learning Community on the Independent Teaching Platform LMS in improving teacher basic competencies and its impact on teacher performance and student learning outcomes. The study used mixed methods with a sequential exploratory model. The qualitative phase was conducted through interviews, focus group discussions (FGDs), observation, and documentation, while the quantitative phase used questionnaires for 55 elementary, junior high, and high school teachers in Wonosobo Regency. Qualitative data analysis was assisted by NVivo 12 software, and quantitative data were analyzed descriptively. The results showed that the Learning Community improved teachers' pedagogical competency with an average score of 3.0 (good category), professional competency of 3.27 (good), personality competency of 3.23 (good), and social competency of 2.77 (fairly good). As many as 67% of teachers participate in Learning Communities due to mandatory requirements and performance assessments, which has shifted the function of learning communities. Learning Communities should serve as a forum for collaboration, reflection, sharing of best practices, and strengthening technological literacy, all of which positively impact teacher professionalism, teaching quality, and student learning outcomes. However, extrinsic motivations are more predominant, focusing more on administrative fulfillment than professional development. The results of this study provide encouragement for learning communities to provide more internal motivation in teacher professional development